2016
DOI: 10.1007/s13337-015-0299-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and phylogenetic study of the fusion genes of Newcastle disease virus from the recent outbreaks in Ahvaz, Iran

Abstract: Newcastle disease (ND) is an acute and highly contagious disease affecting many domestic and wild species of birds. Its effects are most notable in domestic poultry due to their high susceptibility and the potential for severe impacts of an epizootic on the poultry industry. In this study, partial sequences of fusion genes of three Newcastle disease virus (NDV) isolates collected during 2013-14 outbreaks from the vaccinated commercial broiler chicken farms with high mortality around Ahvaz city (Southwest of Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 6 publications
2
10
0
Order By: Relevance
“…Besides, the amino acid sequence for lentogenic isolates is similar to the sequence of the isolates in the present study [21]. Evaluation of amino acid sequence of F0 protein cleavage site of isolates with velogenic Newcastle disease virus (subgenotype VIIb) in Ahmadi et al's (2016) study [1] and Velogenic isolates from the study of Boroomand et al (2016) in Ahvaz also followed the pattern of 112RRQKR/F117 in terms of the amino acid sequence of F0 protein cleavage site [4].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Besides, the amino acid sequence for lentogenic isolates is similar to the sequence of the isolates in the present study [21]. Evaluation of amino acid sequence of F0 protein cleavage site of isolates with velogenic Newcastle disease virus (subgenotype VIIb) in Ahmadi et al's (2016) study [1] and Velogenic isolates from the study of Boroomand et al (2016) in Ahvaz also followed the pattern of 112RRQKR/F117 in terms of the amino acid sequence of F0 protein cleavage site [4].…”
Section: Discussionsupporting
confidence: 68%
“…In recent years, many cases of Newcastle disease have been reported in vaccinated ocks with high antibody levels [4], and on the other hand because the identi cation of Newcastle virus in many valid studies based on protein F0 [21], so in the present study, Newcastle disease virus was isolated from ocks with respiratory symptoms and F gene was detected by Reverse-transcription polymerase chain reaction (RT-PCR). The nucleotide and amino acid sequences of the F gene cleavage site were examined in the recovered isolates.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the amino acid sequence for lentogenic isolates is similar to the sequence of the isolates in the present study [21]. Evaluation of amino acid sequence of F0 protein cleavage site of isolates with velogenic Newcastle disease virus (subgenotype VIIb) in Ahmadi et al's (2016) study [1] and Velogenic isolates from the study of Boroomand et al (2016) in Ahvaz also followed the pattern of 112RRQKR/F117 in terms of the amino acid sequence of F0 protein cleavage site [4]. Ghalyanchi et al (2018) showed that the acute and emerging subgenotype VIIi also follows the pattern of 112RRQKR/F117 in the mentioned area [10].…”
Section: Discussionsupporting
confidence: 57%
“…Genotype VII.1.1 has been isolated from Bulgaria and Ukraine between 2002 and 2013 [ 23 , 25 ]. Iran has reported poultry outbreaks with genotype VII.1.1 and VII.2 [ 27 , 28 ]. These studies conclude that genotype VII is a dominant strain in poultry and wild migratory birds and gradually undergoing adaptive changes, retaining fitness to survive in both immune and naturally exposed birds.…”
Section: Discussionmentioning
confidence: 99%